2019
DOI: 10.36834/cmej.57323
|View full text |Cite
|
Sign up to set email alerts
|

Providing quality feedback to general internal medicine residents in a competency-based assessment environment

Abstract: Construct: Competence Based Medical Education (CBME) is designed to use workplace-based assessment (WBA) tools to provide observed assessment and feedback on resident competence. Moreover, WBAs are expected to provide evidence beyond that of more traditional mid- or end-of-rotation assessments [e.g., In Training Evaluation Records (ITERs)]. In this study we investigate competence in General Internal Medicine (GIM), by contrasting WBA and ITER assessment tools.Background: WBAs are hypothesized to improve and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…The A-CCERR does not require raters for scoring, obviating the need for blinding [21]. Notably, the O-EDShOT demonstrated significantly higher mean CCERR and A-CCERR scores, suggesting that the inability to blind CCERR raters did not bias our results [21,36,37].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 85%
“…The A-CCERR does not require raters for scoring, obviating the need for blinding [21]. Notably, the O-EDShOT demonstrated significantly higher mean CCERR and A-CCERR scores, suggesting that the inability to blind CCERR raters did not bias our results [21,36,37].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 85%
“…Recent studies reported that qualitative narrative, actionable and specific feedback was of great value and facilitated a conversation with more credibility, allowing the learner to be more at ease. 33,34 Existing literature has demonstrated that the trusting relationship fostered by narrative feedback between the assessor and learner enabled an environment that addressed emotional obstacles in facilitating feedback. 34 In keeping with this, the introduction of EPA observations may have indirectly led to prompts for this type of narrative and actionable feedback conversation, which may be more important than the documentation of the feedback event itself.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantitative WPBA practices can result in psychometrically poor results, [6] leading some to advocate for a "post-psychometric" era of assessment in which the subjective and contextual natures of WPBAs are embraced [7][8][9]. This has sparked interest in narrative data as a potentially more useful measure of performance than quantitative assessment data [5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%